2018
DOI: 10.9734/indj/2018/41477
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Quality of Life and Psychiatric Morbidity among School Teachers in Abeokuta,South-West Nigeria

Abstract: Aims: To measure subjective Quality of Life and its relationship to psychiatric morbidity and sociodemographic variables in secondary school teachers in Abeokuta, Ogun state, Nigeria. Study Design: Cross-sectional. Place and Duration of Study: 10 selected public secondary schools in Abeokuta between November 2014 and March 2015. Methodology: The study was carried out among 341 school teachers in two stages. The 1st stage involved the administration of the World Health Organization Quality of Life (WHOQOL-BREF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
0
0
Order By: Relevance
“…In Nigeria, married schoolteachers who have spent the longest number of years in the profession had the overall best QOL among their colleagues. [ 7 ] Besides, the report expresses that flexible working schedules and good interprofessional relationships can have positive effects on the QOL of bank workers in Nigeria. Studies have also shown that work stress from work overload and working overtime was a major reason for self-medication by Nigerian bankers, hence affecting their overall QOL.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, married schoolteachers who have spent the longest number of years in the profession had the overall best QOL among their colleagues. [ 7 ] Besides, the report expresses that flexible working schedules and good interprofessional relationships can have positive effects on the QOL of bank workers in Nigeria. Studies have also shown that work stress from work overload and working overtime was a major reason for self-medication by Nigerian bankers, hence affecting their overall QOL.…”
Section: Introductionmentioning
confidence: 99%